Designing for the commercial exploitation of online identity - Emmanouil, Dialechti Christina (2017)
In our digital era, social networking sites are becoming increasingly relevant to multiple aspects of individuals’ lives, including personal and professional. A group of professionals who heavily rely on these platforms for commercial purposes is book authors, as they use them to connect with readers and promote their books. In their attempts to establish their professional identities in these platforms, they face multiple challenges that public self- presentation carries. Three studies were conducted for this dissertation giving both qualitative and quantitative insights to the ways authors use social networking sites. The findings resulted in the identification of design opportunities that could facilitate online identity management for commercial purposes. The first study surveyed 103 authors about their attitudes and behaviours regarding information sharing via their professional social networking. It found that authors engage in rich self-presentation concerning multiple life aspects but avoid sharing information of a personal nature. This finding led to the development of Layered Identity Theory that represents all identity aspects, both intimate and non-intimate, as layered with inner layers conveying more personal information. Another practice of authors is the management of multiple accounts in a single platform to support different life aspects. There are also authors who use pen names to avoid links between their author selves and their personally identifiable life aspects when publishing their books and managing their social networking. A novel hybrid self-presentation was identified, as there were authors who reported sharing real information about themselves but alter it to prevent their mass audiences from knowing their real name identities. Multiple challenges could rise for them, such as accidentally sharing content in wrong accounts or revealing personally identifiable information. The second study, an online investigation that was based on observing authors’ behaviours in social networking sites, provided insights about authors’ activities across platforms and the content they generate in the most popular ones. The study verified that authors cover a variety of topics about multiple life aspects, including family and relationship; however their sharing cannot be considered personal. This finding established the relevance of Layered Identity Theory to online information sharing. The study also found that authors form online networks and employ their relationships with other users to further establish their professional identities. At the same time, they use social networking sites for creative purposes, such as feedback collection and direct promotion. Indications that authors’ online identity management conveys underlying tensions were identified and discussed. These tensions involve identity incoherence across platforms, difficulties in managing audiences, blurred profiles, and the possibility of negative involvement of others in their self-presentation. The final study, which comprised of two co-design workshops, explored how authors relate to tensions that were previously identified in the studies conducted. In addition, the workshops uncovered authors’ experiences with other users of social networking sites who were negatively involved with their identity management. Managing multiple accounts in a single platform was confirmed by authors as a challenging activity, whereas sharing multiple life aspects was described as a positive common practice among authors when there is an overall balance in the types of information shared. Interestingly, authors’ motivation for sharing multiple life aspects with their online audiences is their desire to attract large audiences and be discovered by publishing companies. Authors acknowledge the underlying tensions that sharing multiple life aspects could generate, such as attracting audiences not interested in writing. When it comes to others’ involvement in their self- presentation, it was found that despite authors’ attempts to balance boundaries between their professional and other life aspects in social networking sites, the information fluidity that characterises the online world makes their different identities come together. Authors acknowledged not being fully aware of the different features that exist in social networking sites; however they had novel design ideas, such as prioritisation and categorisation of generated content, extra layers of security before content sharing, and greater control over others’ content about them. Overall, the findings of this dissertation reveal that even though social networking sites lack features to fully support authors’ self-presentation, the creativity that characterises this group of professionals allows them to use these platforms in ways that partially fulfil their needs; yet remain challenging and need to be facilitated. The studies conducted suggest that many opportunities rise for them online, such as the development of personal relationships with readers and other authors, despite the fact that their self- presentation is based on carefully planned activities. Moreover, the findings uncover that authors establish a new identity aspect online that is formed using a pen name and slightly altered information from their other identity aspects. By identifying Layered Identity Theory to precisely study information sharing online, hybrid self-presentation, as well as other commercial online practices, underlying tensions, and design recommendations, this dissertation raises considerations that could be used to further investigate the commercial use of social networking sites and design relevant supporting technology.